Politics in Decentralization: The Appointment of Metropolitan, Municipal and District Chief Executives (MMDCEs) in Ghana - Adam Mohammed, Abdul-Wadudu (Advances in Social Sciences Research Journal, 2019)
Volumes of studies have examined Ghana’s decentralization. But none has looked at the politics in the appointment of metropolitan, municipal and district chief executives (MMDCEs) – the political heads of the districts in Ghana, which is not only political but partisan and perennially contentious. The objective of this paper is to fill the gap by identifying the political actors in the process of appointing MMDCEs, their interests, the tension and the elements of the political furore among them. Making MMDCEs elective in Ghana is also examined.